2018
DOI: 10.3390/su10040975
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Evolution of Producer Service Sectors and Its Influencing Factors in Cities: A Case Study of Hangzhou, China

Abstract: Producer service industries are an important feature in the current development of a metropolis. Researchers from different countries are increasingly concerned about location changes and the motives of producer service sectors in cities. Given the rapid development of producer service sectors in developing countries, this study examines changes in the distribution of producer service sectors over the past decade and factors influencing them in a case study using the city of Hangzhou in China. Results show tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 62 publications
0
13
0
Order By: Relevance
“…Results show that Hangzhou's producer service sector is still mainly concentrated in the central business district (CBD). However, a distinct trend of diffusion to suburban areas was observed, which formed several secondary clusters on the periphery of the city [21].…”
Section: How To Promote Socio-economic Sustainability In the Smart VImentioning
confidence: 99%
“…Results show that Hangzhou's producer service sector is still mainly concentrated in the central business district (CBD). However, a distinct trend of diffusion to suburban areas was observed, which formed several secondary clusters on the periphery of the city [21].…”
Section: How To Promote Socio-economic Sustainability In the Smart VImentioning
confidence: 99%
“…When recording the sample plots, the steps for determining their geographic coordinates are as follows. (1) The precise four-parcel information is mainly obtained from the information of land bidding, auction, and publicity published on the official website of the Hangzhou Land and Resources Bureau (Figure 2). The location is initially determined in conjunction with Baidu Map.…”
Section: Site Characteristicsmentioning
confidence: 99%
“…Upon its establishment, a city may be viewed as a collection of residential, commercial, industrial, and other multi-functional spaces [1]. Various types of urban land have different roles in urban economy and life, carrying different functions of urban system operations [2].…”
Section: Introductionmentioning
confidence: 99%
“…And during the rapid urbanization process, the urban environment had a more and more negative impact on the surrounding areas (Han et al 2015b). On the other hand, the polycentric urban development, accompanied by consistent growth of population, caused tight environmental stress in the outskirts of the city centres (Sun et al 2012, Han et al 2015a, Wu et al 2018, Sun and Lv 2020. Lin et al found that the decline rate of PM 2.5 in most urban areas was higher than that in other areas .…”
Section: Introductionmentioning
confidence: 99%